KONDISI TEMPAT KERJA BERPENGARUH TERHADAP KINERJA PEGAWAI DI KANTOR BADAN PELAYANAN TERPADU SATU PINTU DAN PENANAMAN MODAL DAERAH (BPTSPPMD) - Yuliasih, Ismayawati (PREDIKSI, 2016)
This study aims to know the influence of working conditions on the performance of employees in the office of the Agency One Stop Services and Investment Board (BPTSPPMD) East Kutai, therefore the researchers to formulate hypotheses